Hyaluronic acid-coated nanoemulsions loaded with a hydrophobic ion pair of all-trans retinoic acid for improving the anticancer activity - Letícia Márcia da Silva Tinoco; Flávia Lidiane Oliveira da Silva; Lucas Antônio Miranda Ferreira; Elaine Amaral Leite; Guilherme Carneiro (Universidade de São Paulo, 2019)
All-trans retinoic acid (ATRA) has been studied for the treatment of cancer, including leukemia and breast cancer. This work aims to develop nanoemulsions (NE) loaded with a hydrophobic ion pair (HIP) of all-trans retinoic acid (ATRA) and a lipophilic amine, stearylamine (SA), and coated with hyaluronic acid (HA) to enhance anticancer activity and reducing toxicity. Blank NE was prepared by spontaneous emulsification and optimized prior to HIP incorporation. NE-ATRA was electrostatically coated with different concentrations of HA. Incorporation of ATRA-SA led to monodisperse NE with small size (129 ± 2 nm; IP 0.18 ± 0.005) and positive zeta potential (35.7 ± 1.0 mV). After coating with 0.5 mg/mL HA solution, the mean diameter slightly increased to 158 ± 5 nm and zeta potential became negative (-19.7 ± 1.2 mV). As expected, high encapsulation efficiency (near 100%) was obtained, confirmed by polarized light microscopy and infrared analysis. Formulations remained stable over 60 days and release of ATRA from NE was delayed after the hydrophilic HA-coating. HA-coated NE-ATRA was more cytotoxic than free ATRA for MDA-MB-231 and MCF-7 breast cancer cell lines, especially in the CD44 overexpressing cells. Blank coated formulations showed no cytotoxicity. These findings suggest that this easily-made HA-coated NE-ATRA formulation is a promising alternative for parenteral administration, thus improving the breast cancer therapy with this drug.